2006
DOI: 10.1093/eurheartj/ehl219
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea inhibits the recovery of left ventricular function in patients with acute myocardial infarction

Abstract: The novel finding is that OSA may inhibit the recovery of LV function in patients with AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 35 publications
2
69
2
5
Order By: Relevance
“…The prevalence of sleep apnoea in the acute phase after a first AMI in the current study is confirmed by several previous studies [5,6,[25][26][27]. NAKASHIMA et al [6] and YUMINO et al [25] performed their sleep studies between 14-21 days after primary PCI, whereas other previous studies used a similar time-point to the present study to assess sleep apnoea at baseline (,5 days after AMI) [5,26,28].…”
Section: Sleep-related Disorders S Buchner Et Alsupporting
confidence: 86%
See 2 more Smart Citations
“…The prevalence of sleep apnoea in the acute phase after a first AMI in the current study is confirmed by several previous studies [5,6,[25][26][27]. NAKASHIMA et al [6] and YUMINO et al [25] performed their sleep studies between 14-21 days after primary PCI, whereas other previous studies used a similar time-point to the present study to assess sleep apnoea at baseline (,5 days after AMI) [5,26,28].…”
Section: Sleep-related Disorders S Buchner Et Alsupporting
confidence: 86%
“…1) Sleep apnoea may contribute to the progression of HF by exposing the heart to intermittent hypoxia, increased pre-load and afterload, sympathetic activation and vascular endothelial dysfunction. For example, in a previous observational study the presence of sleep apnoea early after AMI was linked to impaired recovery of cardiac function [6]. Ultimately, both OSA and CSA confer an increased mortality risk in patients with chronic HF [7][8][9].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…After the first acute myocardial infarction, 65.7% of patients had an apnea-hypopnea index ≥ 15/h 35 . In other studies, the prevalence of OSA in patients with artery heart disease ranged from 43 to 66.4% 36,37,38,39 . The prevalence of a high risk of coronary artery disease associated with OSA in our survey was within these estimates.…”
Section: Discussionmentioning
confidence: 75%
“…To date diagnosis or treatment of sleep apnoea is not part of the recommended or standard care of patients early after acute myocardial infarction [6]. Since sleep apnoea is associated with increased cardiac workload [7] and myocardial damage [8] in the early phase after myocardial infarction, intervention trials are warranted to assess the safety and efficacy of PAP treatment in this time period. @ERSpublications Recovery of left ventricular function after acute myocardial infarction leads to attenuation of sleep apnoea http://ow.ly/kslug…”
mentioning
confidence: 99%